PENGARUH TRANSFER PRICING TERHADAP PENGHINDARAN PAJAK DENGAN MANAJEMEN LABA SEBAGAI VARIABEL INTERVENING - Hendi; Julianti (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
The purpose of carrying out this research is to examine the direct effect of transferpricing on tax avoidance and the indirect effect of transfer pricing on tax avoidancemediated by earnings management. The research sample consisted of 169 nonfinancial companies listed on the IDX-IC sectoral index of the Indonesia StockExchange during the year of observation (2016-2020). Sample selection was doneusing the purposive sampling technique. The research data was overall tested bypanel regression, while mediation effect is tested by sobel test and varianceaccounted for (VAF) test. The results of this study conclude that transfer pricing isnot significant in influencing tax avoidance directly, and the earnings managementis not able and is not significant in mediating the effect of transfer pricing on taxavoidance.